2008
DOI: 10.1299/jsdd.2.540
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Analysis of Elevator Rope (2nd Report, Forced Vibration of Rope with Damping)

Abstract: Elevator ropes in high-rise buildings are forcibly excited by the displacement of the building induced by wind force. An approximate solution to the forced vibration of a rope with time-varying length and having linear damping is presented here. It is assumed that the rope tension and the moving velocity are constant, and that the damping coefficient of the rope is small. Virtual sources of waves which can be assigned to reflecting waves are used for obtaining the approximate solution. Finite difference analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…(3) and (4). It is confirmed that the calculated results from the finite difference analyses are in fairly good agreement with those of the exact solution (4), (5) , in the case where the rope tension and the moving velocity are constant.…”
Section: Response Of Rope Which Resonates While the Elevator Is Movingsupporting
confidence: 74%
See 3 more Smart Citations
“…(3) and (4). It is confirmed that the calculated results from the finite difference analyses are in fairly good agreement with those of the exact solution (4), (5) , in the case where the rope tension and the moving velocity are constant.…”
Section: Response Of Rope Which Resonates While the Elevator Is Movingsupporting
confidence: 74%
“…Numerical analysis is performed by using the following difference equations (4), (5) , derived from Eq. (2).…”
Section: Natural Frequency and Frequency Response Of Elevator Ropementioning
confidence: 99%
See 2 more Smart Citations
“…This study investigates a string with one vibration suppressor. A numerical analysis is performed using the following difference equation (Kimura et al, 2007b(Kimura et al, , 2008, derived from Eq. (21).…”
Section: Equation Of Motion and Finite Difference Analysismentioning
confidence: 99%